Mixed polymer hydrophilic matrices containing HPMC and PEO - Hu, Anran (2016)
The research in this thesis describes investigations of (i) mixed polymer HPMC and PEO hydrophilic matrices and their performance in low and high ionic environments and (ii) understanding the internal behaviour of HPMC and PEO mixed systems. It was postulated that using a blend of these polymers might provide advantages over the use of single polymers. A series of ‘realistic’ 30% w/w polymer matrix formulations, containing different weight ratios of HPMC and PEO and a soluble model drug (caffeine), were tested in ionically challenging media, up to 1M sodium chloride (NaCl). Dissolution testing showed how HPMC dominated formulations exhibited accelerated release in high ionic strength media (0.8M NaCl or higher), whereas PEO dominated formulations did not. Power law analyses suggested the release mechanism of matrices in 0.6M NaCl and below were anomalous non-Fickian transport, but case II transport was observed in HPMC dominated matrices at 0.8M NaCl and above. A polymer ratio of 4:6 HPMC:PEO allowed an extended release tablet to be formulated that was resistant to 1M NaCl. In 0.6M NaCl or below, increasing the proportion of HPMC in a mixed HPMC:PEO tablets, increased the duration of extended release. Confocal laser scanning microscopy was used to investigate the structure of the HPMC:PEO matrix hydrated gel layer. The results provided evidence that HPMC and PEO particles swell independently in the gel layer. They remained substantially unmixed during gel layer formation, and each appeared to contribute independently to gel layer structure. Magnetic resonance imaging showed how PEO matrices hydrated more rapidly than HPMC matrices, but PEO matrices completely dissolved after 9 hours. In the case of 4:6 HPMC:PEO and HPMC matrices, a hydrated gel remained. This reflected the behaviour of these matrices in the dissolution tests. Unfortunately, MRI could only be applied in zero salt media, as the dielectric properties of NaCl interfered with the results, and other techniques were required to examine matrix behaviour in high salt media. Texture analysis showed that at low NaCl concentrations, the HPMC gel layer exhibited higher gel strength than PEO, and that by substituting HPMC for PEO increased gel layer strength was obtained. The later stages of gel layer morphology were also investigated by digital optical macroscopy. Images showed greater gel longevity of HPMC and mixed matrices, with evidence for a higher gel strength and less erosion than PEO matrices. Swelling of single polymer particles showed how increasing NaCl concentration significantly inhibited HPMC particle swelling but only had a limited effect on PEO particle swelling. The ability of PEO particles to swell in high salt media may explain the resistance of PEO matrices to high NaCl dissolution media. The miscibility of HPMC and PEO in dilute solution was studied by rheology and phase contrast microscopy. Measurements of storage modulus (G’) at 1% w/v showed how most polymer mixtures showed negative deviations from ideal mixing at all oscillatory frequencies studied (0.1Hz, 1Hz, and 10Hz). This is evidence that these polymers are immiscible in solution. Phase contrast microscopy provided direct optical evidence of phase separation in blended HPMC:PEO solutions (4% w/v). The tendency of these polymers to be immiscible, suggests that they may also be phase separated in the more concentrated environment of the gel layer. Gel layer morphology in binary polymer tablets was investigated directly by confocal microscopy (up to 15 min) and by attenuated total reflectance Fourier transform infrared spectroscopy (ATR-FTIR) up to 3 hours. The confocal microscopy images showed that HPMC and PEO appeared to swell independently during early gel layer. Each polymer appeared to contribute independently to gel layer structure. ATR-FTIR imaging allowed chemical mapping of the three components (water, PEO and HPMC) in the gel layer, providing evidence that each polymer formed individual domains. PEO appears to be more extensively swollen than HPMC and may form the outer part of the gel layer, protecting HPMC from the effect of high ionic media.